The Impact of Lean Management Implementation on Inpatient Discharge Prescription Services at Pertamina Central Hospital - Hermawati, Ajitya Kurnia; Kristin, Erna; Firman, Firman (Jurnal Kesehatan Masyarakat Indonesia, 2024)
Background: The lead time of inpatient discharge prescription services affects the overall discharge process. In 2022, lead times at Pertamina Central Hospital's Inpatient Pharmacy varied, requiring continuous efforts to meet target times and avoid disrupting discharge plans. This research aims to evaluate the impact of lean management on reducing these lead times. Methods: The study employs a combined quantitative and qualitative research design with an action research approach. It was conducted from March 4 to May 8, 2023, involving pharmacists, pharmaceutical technical personnel, compounders, and pharmacy couriers. Data analysis included measuring lead time changes pre- and post-lean management implementation and narrative analysis of qualitative findings. Results: After implementing lean management, the lead time for non-compounded prescriptions decreased from 42.6 to 25 minutes, with value added ratio (VAR) increasing from 18.9% to 27%. For compounded prescriptions, lead time dropped from 67 to 45.7 minutes, and VAR rose from 25.2% to 37.9%. The Mann-Whitney U test confirmed the significant difference in average lead time. Conclusion: The implementation of lean management in inpatient discharge prescription services has been proven to improve lead time and increase process efficiency (VAR).